Toxicity Assessment of the Xanthid Crab Demania cultripes from Cebu Island, Philippines - Manabu Asakawa; Gloria Gomez-Delan; Shintaro Tsuruda; Michitaka Shimomura; Yasuo Shida; Shigeto Taniyama; Mercy Barte-Quilantang; Jo Shindo (Journal of Toxicology)
Several cases of poisoning resulting in human fatalities and stemming from the ingestion of coral reef crabs have been reported from the Indo-Pacific region. We assessed the toxicity of the unidentified xanthid crab collected from the Camotes Sea off the eastern coast of Cebu Island, central Visayas region of Philippines from the food hygienic point of view. All seven specimens, which were identified with Demania cultripes, collected in 2006 were toxic to mice irrespective of the season of collection and induced paralytic symptoms typical of tetrodotoxin (TTX) and paralytic shellfish poison (PSP). The activity was expressed in mouse unit (MU) being defined as the amount of TTX to kill a 20 g ddY male mice in 30 min after i.p. injection. Toxicity scores for viscera and appendages of specimens were 18.2±16.0 (mean ± S.D.) and 4.4±2.6 MU/g, respectively. The highest individual toxicity scores observed for viscera and appendages were 52.1 and 7.7 MU/g, respectively. The frequency of toxic samples was 100%. Toxin profiles as determined by high-performance liquid chromatography-fluorescent detection analysis (HPLC-FLD) revealed that TTX was the main toxic principle accounting for about 90% of the total toxicity along with 4-epi TTX and 4,9-anhydroTTX. Furthermore, gas chromatography-mass spectrometry (GC-MS) analysis revealed mass fragment ion peaks at m/z 376, 392 and 407, which were characteristic of the quinazoline skeleton (C9-base) specific to TTX. In addition, only a small amount of PSP containing gonyautoxins1–4 and hydroxysaxitoxin was detected. To our knowledge, this is the first report presenting evidence of occurrence of TTX and PSP in the xanthid crab D. cultripes inhabiting waters surrounding Cebu Island. From food hygienic point of view, people in coastal areas should be warned of the potential hazard of this crab in order to prevent its intentional or accidental consumption.